Perkembangan Pembelajaran Bahasa Arab di MTs Pontren Al-Ihsan - wardahtul mujahidah mujahidah; Akmal Walad Ahkas Ahkas (Didaktika Dwija Indria, 2025)
Arabic language learning in madrasah plays a strategic role in shaping students’ basic competencies, especially in Islamic boarding schools where Arabic is the primary language of Islamic studies. This study aims to analyze the development of Arabic language learning at MTs Pontren Al-Ihsan, focusing on curriculum, methods, media, and students’ outcomes. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The findings reveal that Arabic language learning at MTs Pontren Al-Ihsan has undergone significant development. In terms of methods, teachers no longer rely solely on the qawaid tarjamah approach but have begun to implement communicative and practice-based strategies. Regarding media, learning has developed from the use of classical textbooks and turath books to the utilization of simple technology such as projectors and digital applications. These developments have positively impacted students’ proficiency in the four Arabic language skills, although challenges remain, including limited facilities, low student motivation, and the shortage of competent teachers. This study recommends strengthening teacher capacity, improving learning facilities, and integrating traditional and modern methods to ensure the sustainability of Arabic language learning in madrasah.